Magnetic Solid Phase Extraction as a Promising Technique for Fast Separation of Metallic Nanoparticles and Their Ionic Species: A Review of Recent Advances - Ingrid Hagarová (Journal of Analytical Methods in Chemistry)
The widespread use of silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs) in a wide variety of industrial as well as medical sectors is indisputable. This leads to a new concern about their presence in various environmental compartments. Since their negative effect and potential toxicity impact have been confirmed, analytical chemists focus on the development of different procedures for their reliable detection, identification, characterization, and quantification, not only in homogenous and simple matrices but also in complex environmental matrices. However, nanoparticles and their ionic species can coexist and their toxicity may differ; therefore, novel analytical approaches are necessary to monitor not only the nanoparticles but also their ionic species. The aim of this article is to bring a review of recent works where magnetic solid-phase extraction (MSPE) procedures in connection with spectrometric methods were used for separation/preconcentration and quantification of (1) silver and gold ions in various environmental samples, (2) AgNPs and AuNPs in real water samples in the presence of various coexisting ions, and (3) both species (it means Ag ions and AgNPs; Au ions and AuNPs) in real water samples. The results presented herein show the great analytical potential of MSPE procedures in connection with spectrometric methods used in these fields and can be helpful in guiding analytical chemists who aim to work on this subject.